2005
DOI: 10.4067/s0034-98872005000200004
|View full text |Cite
|
Sign up to set email alerts
|

Propuesta de una metodología de análisis de la calidad global de la alimentación

Abstract: The HEI is a tool that can be used in the Chilean population and can be used to assess the effectiveness of health promotion initiatives. It also can help to focalize educational programs to specific nutrients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 11 publications
2
2
0
10
Order By: Relevance
“…The HEI score (59.7) revealed by the present study was similar to that found in population studies of adolescents performed in municipal districts in the state of São Paulo 11,15 , and in Chile 16 . It was slightly lower than the score verified in the study by Fernández et al 17 , of adolescents in the city of Guadalajara (Spain) and that found for North American adolescents by Goodwin et al 18 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The HEI score (59.7) revealed by the present study was similar to that found in population studies of adolescents performed in municipal districts in the state of São Paulo 11,15 , and in Chile 16 . It was slightly lower than the score verified in the study by Fernández et al 17 , of adolescents in the city of Guadalajara (Spain) and that found for North American adolescents by Goodwin et al 18 .…”
Section: Discussionsupporting
confidence: 89%
“…These findings are consistent with other Brazilian studies that also observed low intake of fruits, vegetables and milk and dairy products in the diet of adolescents 3,11,15 . The component with the highest score was meat and eggs, a result similar to the findings of studies of adolescents in other countries 16,17 and some municipal districts in the state of São Paulo 15 . In the present study, adolescents from the segment of higher family income had a lower consumption of the group cereals and derivatives, as verified by Levy-Costa et al 21 using data from the "Pesquisa de Orçamentos Familiares" (Household Food Budget Survey -HFBS) to evaluate the evolution of food consumption in the metropolitan areas of Brazil.…”
Section: Discussionsupporting
confidence: 87%
“…A média de pontos do IQD foi inferior à média dos dados norte-americanos, para as faixas etárias de 5 a 14 anos (68,4) e 15 a 39 anos (60,2) 19 . Isso também foi observado quando comparada aos dados obtidos por Feskanish et al 10 , ao analisar a dieta ingerida de 426 adolescentes norte-americanos do sexo feminino, de 11 a 14 anos, e 425 do sexo masculino de mesma idade, em que foi constatada, por meio do Healthy Eating Index (HEI), média de pontuação de 63,5 e 62,2, respectivamente.…”
Section: I S C U S S ã Ounclassified
“…Isso também foi observado quando comparada aos dados obtidos por Feskanish et al 10 , ao analisar a dieta ingerida de 426 adolescentes norte-americanos do sexo feminino, de 11 a 14 anos, e 425 do sexo masculino de mesma idade, em que foi constatada, por meio do Healthy Eating Index (HEI), média de pontuação de 63,5 e 62,2, respectivamente. Além disso, porcentagem significativa de indivíduos apresentou dieta inadequada (28%), com resultado similar ao estudo realizado por Pinheiro & Atalah 19 no Chile, com adaptação do HEI à 22 , em que, comparativamente, os meninos mostraram maior ingestão desse nutriente do que as meninas, sendo que, aproximadamente, 50% da população estudada apresentou consumo elevado de colesterol. Capper et al 23 também encontraram ingestão de colesterol acima do recomendado, em pesquisa realizada nos Estados Unidos com 200 adolescentes.…”
Section: I S C U S S ã Ounclassified
“…El climaterio puede suponer una etapa de consolidación de los hábitos alimentarios que practicado de forma correcta ayuden a prevenir y a moderar algunos problemas como lo ya descritos (2)(3)(4). Diseñar, realizar o evaluar programas de salud que pretendan lograr mejorías en la calidad de vida de las mujeres, requiere del desarrollo de instrumentos adecuados para esos objetivos (12,13). En este sentido indicadores dietéticos como el grado de suficiencia de la dieta (adecuación de calorías y nutrientes críticos) y el índice de alimentación saludable (IAS) en distinta época del año, deberían ser descritos para este grupo de edad ya que pueden constituir un aporte valioso al diagnóstico alimentario nutricional, permitiendo la identificación de factores alimentarios protectores de la salud o de riesgo de enfermar (14).…”
unclassified